Unexpected Risk Factors of Premature Rupture of Membranes in Independent Midwife Practice: A Contradiction to Existing Theory - Marlina, Marlina; Trinovadela, Nora Isa; Trianingsih, Indah; Putriana, Yeyen (Poltekkes Kemenkes Tanjung Karang, 2025)
The incidence of premature rupture of membranes (PROM) is still one of the critical problems in obstetrics that increases maternal and neonatal morbidity and mortality. This study aims to investigate the relationship between anemia, parity, and chronic energy deficiency (CED) and the incidence of premature rupture of membranes (PROM) in the Independent Midwife Practice (PMB) setting at the Sukarame Health Center area, Bandar Lampung City. The study design used was cross-sectional. The subjects were 137 mothers giving birth in the PMB area of Sukarame Health Center, Bandar Lampung City in 2024. Data collection was carried out using primary data from interviews with mothers giving birth in PMB in the Sukarame Health Center area, Bandar Lampung City. Data analysis used univariate and bivariate data analysis with the Chi-Square test. The results showed that there was no significant relationship between parity and premature rupture of membranes (p-value: 0.637). However, there were significant relationships between anemia (p-value: 0.017) and CED (p-value: 0.029) and PROM in PMB. Interestingly, the results showed that PROM was more common in mothers without anemia and without CED. Although anemia and CED are conventionally considered risk factors for PROM, this study found a higher incidence of PROM among mothers without anemia and without CED. Therefore, antenatal care should not only focus on preventing anemia and CED but also on identifying other hidden risk factors such as infections, stress, and physical strain, even in seemingly healthy pregnancies.